Taking the high road? Compliance with commuter tax allowances and the role of evasion spillovers - Jörg Paetzold; Hannes Winner (University of Salzburg, Department of Social Sciences and Economics, 2016)
This paper provides evidence of evasion in the context of a widely used commuter tax allowance, and explores evasion spillovers as a determinant of the individual compliance decision. For this purpose, we exploit discontinuities in the commuter allowance scheme and employ a research design resting on a large panel of individual tax returns. We find that around 30 percent of all allowance claims are overstated and, consistent with deliberate tax evasion, we observe sharp reactions of taxpayers to thresholds where the allowance discretely jumps to a higher amount. Further, we use variation in job changes to uncover spillover effects from the work environment on the individual compliance decision. These effects appear to be asymmetric: Job changers moving to companies with a higher fraction of cheaters increase their cheating. In contrast, movers to companies with a lower fraction of cheaters tend not to alter their reporting behavior. We provide suggestive evidence that the spillover has more to do with an information environment, but can ultimately not reject other behavioral explanations such as asymmetric persistence of norms.
Keywords: H24; H26; D83; 330; Tax Evasion; Self-Reporting; Tax Deductions; Spillover Effects